2012
DOI: 10.3390/ijms13055406
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Phytotoxicity and Antioxidant Activity of Selected Flavonoids

Abstract: The knowledge of flavonoids involved in plant-plant interactions and their mechanisms of action are poor and, moreover, the structural characteristics required for these biological activities are scarcely known. The objective of this work was to study the possible in vitro phytotoxic effects of 27 flavonoids on the germination and early radical growth of Raphanus sativus L. and Lepidium sativum L., with the aim to evaluate the possible structure/activity relationship. Moreover, the antioxidant activity of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 45 publications
5
43
0
Order By: Relevance
“…Cai and others (2006) evaluated the structure-radical scavenging activity relationships of flavonols, flavones, flavanones, and isoflavones from the traditional Chinese medicines by ABTS assay and DPPH assay and the results were expressed in terms of TEAC (mM). Quercetin and kaempferol appears higher and OH groups reduced the DPPH free radical scavenging potential (De Martino et al, 2012;Wang et al, 2012b;Sarkar et al, 2012;Om et al, 2008;Rice-Evans et al, 1996;Cai et al, 2006). …”
Section: O-glycosylationmentioning
confidence: 96%
“…Cai and others (2006) evaluated the structure-radical scavenging activity relationships of flavonols, flavones, flavanones, and isoflavones from the traditional Chinese medicines by ABTS assay and DPPH assay and the results were expressed in terms of TEAC (mM). Quercetin and kaempferol appears higher and OH groups reduced the DPPH free radical scavenging potential (De Martino et al, 2012;Wang et al, 2012b;Sarkar et al, 2012;Om et al, 2008;Rice-Evans et al, 1996;Cai et al, 2006). …”
Section: O-glycosylationmentioning
confidence: 96%
“…e mixtures of chemical substances present in the C. langsdor i leaf extracts (composed mostly of avonoids) could alter membrane integrity and polarity as well as the function of transport proteins (Hedrich, 2012;Martino et al 2012). is could explain the phenotypic characteristics found in seedlings treated with WSE, where the roots were extremely short and deformed.…”
Section: Discussionmentioning
confidence: 88%
“…Martino et al (2012) showed that the e ect of various avonoids on initial root growth was substantially inhibited, while germination was only slightly a ected.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of these plants amongst others used for malaria treatment is not unconnected with the antioxidative stress exhibited by the plants, which is directly linked with antioxidant potential of several phytochemicals of the plants species [4,7,12,[25][26][27][28] . Previous studies have shown that the plants was multipurpose species in African folk medicine in the treatment of several diseases conditions.…”
Section: Discussionmentioning
confidence: 99%